The Free Radical Scavenger N-Tert-Butyl-α-Phenylnitrone (PBN) Administered to Immature Rats During Status Epilepticus Alters Neurogenesis and Has Variable Effects, Both Beneficial and Detrimental, on Long-Term Outcomes - Kubová, Hana; Folbergrová, Jaroslava; Rejchrtová, Jana; Tsenov, Grygoriy; Pařízková, Martina; Burchfiel, James; Mikulecká, Anna; Mareš, Pavel (Frontiers in cellular neuroscience, 2018)
Status epilepticus (SE), especially in immature animals, is known to produce recurrent spontaneous seizures and behavioral comorbidities later in life. The cause of these adverse long-term outcomes is unknown, but it has been hypothesized that free radicals produced by SE may play a role. We tested this hypothesis by treating immature (P25) rats with the free radical scavenger N-tert-butyl-α-phenylnitrone (PBN) at the time of lithium chloride (LiCl)/pilocarpine (PILO)-induced SE. Later, long-term outcomes were assessed. Cognitive impairment (spatial memory) was tested in the Morris water maze (MWM). Emotional disturbances were assessed by the capture test (aggressiveness) and elevated plus maze's (EPM) test (anxiety). Next, the presence and severity of spontaneous seizures were assessed by continuous video/EEG monitoring for 5 days. Finally, immunochemistry, stereology and morphology were used to assess the effects of PBN on hippocampal neuropathology and neurogenesis. PBN treatment modified the long-term effects of SE in varying ways, some beneficial and some detrimental. Beneficially, PBN protected against severe anatomical damage in the hippocampus and associated spatial memory impairment. Detrimentally, PBN treated animals had more severe seizures later in life. PBN also made animals more aggressive and more anxious. Correlating with these detrimental long-term outcomes, PBN significantly modified post-natal neurogenesis. Treated animals had significantly increased numbers of mature granule cells (GCs) ectopically located in the dentate hilus (DH). These results raise the possibility that abnormal neurogenesis may significantly contribute to the development of post-SE epilepsy and behavioral comorbidities.
Keywords: epilepsy; juvenile rats; free radical scavenger; adult neurogenesis; epileptic comorbidities; neuroprotection